The Mediating Role of Innovation Capability in the relationship between Supply Chain Management and Firm Performance - Opaleye, Muyiwa Adeleke; Opaleye, Adepeju Abimbola; Adelugba, Iyabode Abisola; Babatunde, Olayinka Funmi (American Journal of Business Science Philosophy, 2025)
In today’s dynamic and competitive business environment, organizations adopt supply chain management to boost innovation and improve performance. This study investigates the linkbetween supply chain management and firm performance and the mediating role of innovation capability. A cross-sectional survey research design was employed; 5 textile firms in Lagos State were conveniently selected for the study. 353 structured questionnaires were administered to top-, middle-, and lower-level managers of the selected firms, of which only 328 were returned. After data screening, only 312 responses were valid for analysis. The study employed SPSS statistical software to perform both descriptive and inferential statistical analysis. The mediation aspect of the analysis was done using Model 4 of the SPSS PROCESS macro. The study found that supply chain management has a significant positive effect on firm performance and innovation capability. Also, innovation capability significantly influences firm performance and plays a mediating role in improving the relationship between supply chain management and firm performance. The study recommends that leaders from industry should prioritize investments in SCM practices that can bring supply chain partners together to build a strong IC for performance improvement.